The Intention of Generation Y to Use Grab car service in UNIMAS - Lim, Sien Nar (Universiti Malaysia Sarawak (UNIMAS), 2019)
Transportation industry is changing quickly in recent years. The increased ability of location data and continuously-increasing number of application, together with other information and communication (eg: ecommerce, telecommunication) are transforming transportation supply and demand in many ways (Alemi, 2018). Grab are the most rapidly growing ride-hailing service in Southeast Asia who started by Anthony Tan and Tan Hooi Ling in 2011. Grab has also become the trend as people nowadays intended to use Grab car service rather than traditional taxi, especially Generation Y. This study is aimed to examine the behavioral intention of Generation Y to use Grab car service in UNIMAS. A total 330 sets of questionnaire were being distributed to Third year students from Faculty Economics and Business in UNIMAS. Demographic profile, behavioral intention of using Grab car service and perception towards Grab car service on the four perceived variables were asked in the questionnaires. The collected data were analyzed by Descriptive analysis, Reliability test, Factor analysis and regression analysis. The results showed there are significant relationship between perceived price and advantages, perceive convenience and percieve accessibility and the behavioral intention and actual using. Besides, perceived safety and security is the major limitation of in UNIMAS. Furthermore, this research study provides useful and important information for both UNIMAS and Grab Company so that further upgrading on safety and security dimension can be improved in addressing the needs of the users.